Microlicia rubra (Melastomataceae), a remarkable new species from Goiás, Brazil - Ferreira-Alves, Rodolfo; Romero, Rosana (Phytotaxa, 2020)
Microlicia rubra, endemic to Serra do Tombador, state of Goiás Brazil, is described here and compared with similar species. The new species is characterized by thick branches, sessile leaves clustered at the apex of the branches, red color of the petals, filaments, pedoconnective and style. It resembles Microlicia stenodonoides and Stenodon suberosus, both endemic to the state of Goiás, Brazil. Description, taxonomic comments, comparisons with similar species, as well as data on geographic distribution, habitat and conservation status are provided.